Pernikahan Sandung Makam Di Temanggung Dalam Perspektif Antropologi Hukum Islam - Rifqiyanto, Agus Ilham; Mafiah, Yeni (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
This research examines marriage in front of a corpse in the Temanggung community, known as nikah sandung makam. The main question asked is how the practice of nikah sandung makam is viewed from the anthropological perspective of Islamic law. Through a qualitative approach with interview and observation methods, this study found that nikah sandung makam has been a culture of the Temanggung community for a long time, this practice is responded to customarily by the community as a form of response to a sense of loss and respect for parents who died. The results show that sandung makam marriages illustrate the diverse relationship between legal and cultural pluralism, and create a new space of thought in the field of Islamic legal anthropology. The legal anthropology approach emphasizes that a culture should not be judged based on whether it violates religious teachings or not, this has no effect as long as there are still many people who practice and believe in the goodness of the tradition. Meanwhile, from the perspective of Islamic law, this practice is considered valid because the pillars and conditions of marriage regulated in Islamic law have been fulfilled.